Emotional Intelligence and Participation in Dhuha Prayer at the Class Level: A Descriptive Correlational Study among Islamic Junior High School Students - Fawwaz Adzansyah Islamy; Yatny Mariam Lestari; Fiki Febriani; Nur’aeni Nur’aeni (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Emotional intelligence (EI) plays a crucial role in students’ character development and academic success. In the context of Islamic education, religious habituation such as Dhuha prayer is viewed not only as a spiritual practice but also as a means of strengthening self-regulation and emotional management. This study aimed to examine the relationship between emotional intelligence and participation in Dhuha prayer at the classroom level in an Islamic junior secondary school (Madrasah Tsanawiyah). The study employed a quantitative approach with a descriptive-correlational design. The population consisted of all students of MTs Muhammadiyah 04 Purbalingga, with a sample of 113 students selected through convenience sampling. Emotional intelligence was measured using the Emotional Intelligence Scale (EIS), while data on Dhuha prayer participation were obtained from class attendance records. Data analysis was conducted at the classroom level by calculating the mean EI scores and average Dhuha prayer participation, followed by Spearman correlation analysis. The results revealed a very strong positive association between mean emotional intelligence and Dhuha prayer participation across classes (ρ = 1.00; N = 3). This association reflects a consistent pattern at the class level and should be interpreted cautiously due to the limited number of analytical units and the correlational nature of the study. This research contributes theoretically to the literature on emotional intelligence and religious practices and provides practical implications for strengthening character education through structured religious habituation programs in schools.